Current Use and Barriers to Healthcare Service Utilization Among Afghan Women Refugees: A Mixed-Method Study - Zahra Moudi; Sedighe S. Mollashahi; Narges Nouri; Maryam Zaboli; Leyla Arabnezhad (Iranian Journal of Nursing and Midwifery Research)
Background: In Iran, Afghan women should be able to use the same maternal services provided to natives. Improvement of the utilization of maternal healthcare services (MHCS) requires knowledge of the specific needs of refugees. In this regard, the present study aimed to explore current use and barriers to healthcare service utilization among Afghan women refugees. Materials and Methods: This sequential explanatory study with a mixed-method design combined two sources of data, namely quantitative data based on data routinely collected from March 2022 to March 2023 in Zahedan city and qualitative data collected from interviews with Afghan women (n = 10) and local managers (n = 6). Purposeful sampling was used to select Afghan women refugees from birth centers. Inductive thematic analysis was used for qualitative data. Results: Only 7% of Afghan women attended antenatal care five times or more at 37–39 weeks of pregnancy. Moreover, 20.45% of Afghan women used traditional birth attendants in their recent birth (F1 = 3764.01, p < 0.001). Qualitative data showed that financial barriers (especially lack of insurance and low family income) were the most important barriers to poor access to antenatal and hospital services. In addition, obtaining poor or insufficient care was another barrier to the use of care. Conclusions: The findings highlighted that Afghan women face different barriers to utilizing MHCS. These barriers should be addressed through collaboration between regional, national, and international agencies to provide community-based interventions, address the health needs and expectations of the local community, and improve the utilization of MHCS.